2021
DOI: 10.1186/s13287-021-02194-z
|View full text |Cite
|
Sign up to set email alerts
|

The role and mechanism of mitochondrial functions and energy metabolism in the function regulation of the mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells that show self-renewal, multi-directional differentiation, and paracrine and immune regulation. As a result of these properties, the MSCs have great clinical application prospects, especially in the regeneration of injured tissues, functional reconstruction, and cell therapy. However, the transplanted MSCs are prone to ageing and apoptosis and have a difficult to control direction differentiation. Therefore, it is necessary to effectively regulate the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 121 publications
0
33
0
Order By: Relevance
“…Studies have reported that stem cells mainly rely on glycolysis for metabolism [ 34 ]. The differentiation of MSCs is accompanied by the decrease of mitochondrial glycolysis and the increase of OXPHOS, this bioenergy conversion plays an important role in the differentiation of MSCs [ 35 ]. The up-regulation of mitochondrial biogenesis and OXPHOS are the characteristics of MSC differentiation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that stem cells mainly rely on glycolysis for metabolism [ 34 ]. The differentiation of MSCs is accompanied by the decrease of mitochondrial glycolysis and the increase of OXPHOS, this bioenergy conversion plays an important role in the differentiation of MSCs [ 35 ]. The up-regulation of mitochondrial biogenesis and OXPHOS are the characteristics of MSC differentiation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial quality and biogenesis are indispensable factors for proper muscle function, as impaired mitochondrial activities lead to muscle atrophy via the activation of various catabolic pathways [ 9 , 20 ]. Healthy mitochondria always maintain muscle homeostasis by producing adequate adenosine triphosphate (ATP) via the tricarboxylic acid cycle and oxidative phosphorylation (OXPHOS) [ 21 ]. They also regulate the antioxidant defense system and apoptosis (a type of programmed cell death).…”
Section: Introductionmentioning
confidence: 99%
“…They also regulate the antioxidant defense system and apoptosis (a type of programmed cell death). Moreover, the biogenesis of mitochondria is regulated by the peroxisome proliferator-activated receptor-gamma coactivator 1-alpha (PGC-1α), which activates nuclear respiration factors (Nrf1 and Nrf2) and the estrogen-related receptorα, which further activates the mitochondrial transcription factor A (TFAM) to promote mitochondrial DNA (mtDNA) replication [21]. Furthermore, myogenesis plays a vital role in the preservation of muscle health and the attenuation of atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Forni et al also reported up-regulated mitochondrial fusion during the adipogenic or osteogenic differentiation of MSCs, while chondrogenic differentiation requires increased expression of mitochondrial fission-related genes [37]. Given that most studies demonstrated only the inverse proportion of mitochondrial fission and fusion, the simultaneous increase and decrease in DRP1 and MFN1/2 under TNF-α/IFN-γ exposure provides a new perspective on the more systemic landscape of mitochondrial dynamics in impaired stem cells and requires more detailed research [32,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial distribution can also be considered a crucial marker for MSC differentiation [38]. Quinn et al reported that undifferentiated MSCs exhibit a perinuclear arrangement of the mitochondria around the nucleus and are uniformly distributed in the cytoplasm [40].…”
Section: Discussionmentioning
confidence: 99%